Portrait of a Town Called Penny Hill - Fecho, Susan B. (My University, 1988)
This written report of creative thesis is an account of the development of a body of work based on the town of Penny Hill, North Carolina. This report conveys a poetical impression of the intimate spaces of the structures at Penny Hill and focuses on the effects that time and the aging process has had on the buildings. Excerpts from Emily Dickinson’s poetry are included as supportive material. This thesis explores the possibilities of using traditional collograph techniques with collage for the purpose of embellishing and enriching the surfaces. it recounts the problems and questions involved in the working process as well as their solutions and answers.
Keywords: North Carolina; Architecture; Picturesque in architecture; Penny Hill